Construction and Evaluation of an Instrument to Measure Content Knowledge in Biology: The CK-IBI - Jörg Großschedl; Daniela Mahler; Ute Harms (MDPI AG, 2018)
The teaching process is well described as an interaction between teacher, student, and content. Thus, it seems obvious that teachers must know the content to help students to learn it. Instruments have been developed to measure teachers’ content knowledge (CK) in biology, but few of them have been provided to the scientific community. Furthermore, most of them have a topic-specific approach, so there is a need for a more comprehensive measure. In efforts to meet this need we have developed an instrument called the CK in biology inventory (CK-IBI), which has a broader scope than previously published instruments and covers knowledge of five biological disciplines (i.e., ecology, evolution, genetics and microbiology, morphology, and physiology). More than 700 pre-service biology teachers were enrolled to participate in tests to assess the instrument’s objectivity, reliability, and validity in two cross-sectional evaluations. Item and scale analyses as well as validity checks indicate that the final version of the CK-IBI (37 items; Cronbach’s α = 0.83) can be scored objectively, is unidimensional, reliable, and validly measures pre-service biology teachers’ CK. As the instrument was used in a German context, it has been translated into English to enable its scrutiny and use by international communities.